Dateringen af den yngre tekst om hellig Niels af Aarhus - Clausen, Svend (Historisk Tidsskrift, 2024)
The date of the younger vita of St. Niels of Aarhus St. Niels of Aarhus (d. 1180) was a local Danish saint from Aarhus diocese. Two anonymous vitae with accompanying short accounts of his miracles exist: an older one (the A-Legend) and a younger one (the B-Legend). Close textual analysis indicates that the A-Legend must be from 1250–1254, while the composition of the B-Legend has been fixed at around 1350 because it mentions Trugot, a canon of the cathedral chapter, and another canon and cantor named John. Both identities appear in another source from the year 1345. Based on new evidence, it can be determined that Cantor John’s time in office lies somewhere between 1325 and 1354. Meanwhile, the B-Legend describes Trugot as a deacon studying in Paris. The cathedral statutes of 1345 stipulated two years of university studies before a cleric could benefit from the estates of the chapter as elected canon and, as Trugot appears in the above-mentioned source from 1345 as a fully qualified canon, he must have been ‘a deacon studying in Paris’ before 1345. Hence, the date of the B-Legend can be moved from around 1350 to somewhere between 1325 (the earliest possible date Cantor John became a canon) and 1345 (the latest possible date for Trugot’s return to Denmark after his studies in Paris).